MATHEMATICAL FORMULATION OF THE PROCESS OF SUSPENSIONS FILTRATION THROUGH FLAT POROUS PARTITIONS - Bredihin, Vladimir Viktorovich; Akulshin, Alexander Anatolyevich; Bredihina, Natalia Vladimirovna (Journal of Applied Engineering Science, 2017)
This paper presents the mathematical formulation of the process of filtering suspensions being formed as a result of semiconductor products manufacturing from gallium arsenide, using flat porous partitions. To develop the methods of production units calculation, there has been conducted an analysis of data found in the literature and the obtained dependencies.